1996
DOI: 10.1111/j.1365-2222.1996.tb00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal challenge with interleukin‐8 causes tissue oedema and neutrophil accumulation in atopic and non‐atopic human subjects

Abstract: This study demonstrates that in human skin, IL-8 induces increased microvascular permeability and neutrophil infiltration, but not eosinophil or T-lymphocyte chemoattraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…However, at the site 1 cm away from allergen injection, there was little staining for adhesion molecules and no inflammatory cell accumulation. This was somewhat of a surprise considering that the levels of IL-6 and IL-8, both of which have been reported to increase adhesion molecule expression and inflammatory cell accumulation (Borish et al, 1989;Douglass et al, 1996), were similar to those recovered from the site of allergen injection. Further, while endothelial cells are good producers of the NF-kB-stimulated cytokines, IL-6 and IL-8, the generation of these cytokines is often accompanied by other NF-kB-stimulated products, including the adhesion molecules ICAM-1 and VCAM-1 (Lin et al, 2005).…”
Section: Discussionmentioning
confidence: 86%
“…However, at the site 1 cm away from allergen injection, there was little staining for adhesion molecules and no inflammatory cell accumulation. This was somewhat of a surprise considering that the levels of IL-6 and IL-8, both of which have been reported to increase adhesion molecule expression and inflammatory cell accumulation (Borish et al, 1989;Douglass et al, 1996), were similar to those recovered from the site of allergen injection. Further, while endothelial cells are good producers of the NF-kB-stimulated cytokines, IL-6 and IL-8, the generation of these cytokines is often accompanied by other NF-kB-stimulated products, including the adhesion molecules ICAM-1 and VCAM-1 (Lin et al, 2005).…”
Section: Discussionmentioning
confidence: 86%
“…IL-8 is a chemokine that plays an important role in neutrophil inflammatory responses including upregulation of neutrophil expression of CD11b and shedding of L-selectin, steps necessary for firm adhesion to endothelial cells and movement into tissue (Hoch et al, 1996;Mukaida et al, 1998). In addition, IL-8 is expressed in tissue with neutrophilic infiltrates and injection of IL-8 into skin results in the accumulation of neutrophils (Lira et al, 1994;Douglass et al, 1996;Murphy, 1997). We previously demonstrated that neutrophils in patients with DH have elevated expression of CD11b, a decreased expression of L-selectin and increased function of neutrophil Fc IgA receptor (Smith et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Lifespan and size of large animals are more similar to men than to rodents, as is their developmental, innate, and mucosal immunity. For instance, mice lack the gene encoding for the interleukin-8 (Hol et al, 2010), a cytokine implicated in severe neutrophilic asthma and in respiratory virus-induced asthma exacerbations (Nakagome et al, 2012;Rohde et al, 2014), and also essential for neutrophil recruitment in men, cattle, and horses (Caswell et al, 1999;Caswell et al, 2001;Cook et al, 2009;Douglass et al, 1996;Franchini et al, 1998;Kaur and Singh, 2013).…”
Section: Development Of Animal Models Better Mimicking Human Diseasesmentioning
confidence: 99%